2010
DOI: 10.1016/j.jcrs.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of hydrophilic acrylic intraocular lenses in combined phacovitrectomy surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 16 publications
3
28
0
1
Order By: Relevance
“…A previous study analyzing an opacified hydrophilic acrylic AcquaSense ® (Ophthalmic Innovative International, USA) IOL described the presence of calcium deposits on the surface and within the substance of the IOL optic and haptics (10) . Similarly to this and other studies regarding hydrophilic lenses, microscopic examination of the five Ioflex ® IOLs revealed that the opacification was due to calcium granular deposits on the surface and within the optic and haptics of the lenses (7,8,10) . Two histochemical methods for calcium detection were used in these cases, and both of them yielded positive results, confirming the calcified nature of the deposits.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A previous study analyzing an opacified hydrophilic acrylic AcquaSense ® (Ophthalmic Innovative International, USA) IOL described the presence of calcium deposits on the surface and within the substance of the IOL optic and haptics (10) . Similarly to this and other studies regarding hydrophilic lenses, microscopic examination of the five Ioflex ® IOLs revealed that the opacification was due to calcium granular deposits on the surface and within the optic and haptics of the lenses (7,8,10) . Two histochemical methods for calcium detection were used in these cases, and both of them yielded positive results, confirming the calcified nature of the deposits.…”
Section: Discussionsupporting
confidence: 80%
“…Calcification on the surface and in the substance of the lens in hydrophilic acrylic IOLs has been well documented (6)(7)(8)(9)(10) . However, to the best of our knowledge this is the first peer-reviewed report on opacification of the Mediphacos Ioflex ® IOL.…”
Section: Discussionmentioning
confidence: 99%
“…Even though migration of gas or silicone oil into the anterior chamber through the zonular fibers is possible, their presence in the anterior chamber was not necessarily observed in the cases we received or the cases described in the literature. 20,28,29 This current study also clearly demonstrates that the distinctive pattern of localized calcification is not associated with a particular IOL design or manufacturer. In summary, the cases described in our study as well as in others warrant consideration to avoid use of hydrophilic acrylic IOLs when procedures using intracameral air or gas, particularly DSEK or DSAEK, are anticipated.…”
Section: Discussionsupporting
confidence: 55%
“…A,B Vitreous tamponade with gas or silicone oil has also led to localized anterior surface calcification, as in 1 of the cases described by Dhital et al 20 and in 2 cases each after combined vitrectomy and cataract surgery described by Lee et al 28 and Walker et al 29 Migration of gas or silicone oil into the anterior chamber via zonular fiber defects remains a possibility after vitreous tamponade, as the pattern of calcification in all these cases suggests a change initially localized to the area of the IOL surface in direct contact with the anterior chamber contents.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to recognize the process involved in IOL opacification; otherwise, surgeons might perform unnecessary surgical procedures such as neodymium:YAG (Nd:YAG) posterior capsulotomies or vitrectomies in eyes in which the opacification is in the IOL itself and not in the posterior capsule or vitreous. 3,4 LABORATORY FINDINGS Gross examination of the explanted IOLs showed a white discoloration of the specimens. Microscopic examination showed dense deposits forming an almost continuous crust, mostly on the anterior surface of the optic component.…”
mentioning
confidence: 99%